Peran Mahasiswa PPKN FIS Universitas Negeri Medan Dalam Menghadapi Tantangan Politik 2024, Studi Kasus: Praktek Money Politik - Linton Naibaho; Johan Pardamean Simanjuntak; Yana Sebha Pasaribu; Roselli Anjelina Lumbansiantar; Nelly Moria Hutapea; Ivana Theo Philia; Kania Nova Ramadhani; Tri Santa Mahulae (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Money Politics is an attempt to bribe voters by providing money or services so that voters' vote preferences can be given to a briber. Political money is no longer surprising, it is a common thing that happens when it comes to elections, parties do various things to get votes from the people, this political money has been passed down from generation to generation. Violations that often occur during elections include the widespread practice of money politics. Money politics is considered a practice that injures democracy. Elections are a big party in democracy where every citizen is free to give their voting rights to the parties that are nominating. In the lead up to the election, many candidates are chosen by the party to take part in the community by giving gifts. This is what we often refer to as